Solitary Fibrous Tumors of the Head and Neck: A Single‐Institution Study of 52 Patients. Issue 3 (12th July 2022) - Chung, Hye Rhyn; Tam, Kenric; Han, Albert Y.; Obeidin, Farres; Nakasaki, Manando; Chhetri, Dinesh K.; St John, Maie A.; Kita, Ashley E.
Abstract : Objective: To evaluate the clinicopathologic characteristics of head and neck solitary fibrous tumors and features that may predict tumor recurrence. Study Design: Retrospective review. Setting: University of California–Los Angeles Medical Center. Methods: A single‐center retrospective study was conducted on pathologically confirmed cases of head and neck solitary fibrous tumors between 1996 and 2021. Patient demographics, clinical course, and histopathologic features were evaluated. Recurrence‐free survival was estimated via Kaplan‐Meier analysis. Results: A total of 52 patients were reviewed. The average patient age was 54.7 years (range, 15‐89). The most common subsite was the orbit (53.8%, n = 28), but other involved areas included the nasopharynx, paranasal sinuses, and scalp. The median tumor size was 2.95 cm (range, 1.3‐11.2). Strong STAT6 (100%) and CD34 (97.9%) expression was observed on immunohistochemistry. Almost all patients were initially managed with wide local excision; 82% of patients (n = 14) had positive margins on pathologic review; and 15% (n = 4) had recurrence at a median 28.5 months (range, 10‐113). White patient race was the only significant predictor of tumor recurrence. Patient age (≥55 years), tumor size (≥4), high mitotic rate, and disease subsite were not associated with recurrence. Conclusion: Head and neck solitary fibrous tumors demonstrate a significantly larger local recurrence rate as compared with their rate of metastasis. They can recur many years following initial therapy, warranting long‐term surveillance and follow‐up to assess for tumor recurrence.